Eros in Sylvia Plath`s Selected Poems - Saeed, Ismael Muhamad Fahmi; Muhamad, Ranji Shorsh Rauf (Sulaimani Journal for Humanities, 2019)
This paper is an extract from a PhD dissertation which is entitled “Eros and Thanatos: A Study in Selected Poems of Sylvia Plath and Anne Sexton”. Plath’s early poems include those poems which are written by Plath from 1956 to 1961; from the beginning of her marriage to Ted Hughes until her separation. In this period, which is called the calm and brighter period, Plath is very pleased with her husband. As she looks at her husband as her father, during this period she thinks of her father as a great and holy person. In her early poems like "Full Fathom Five” and "The Colossus" , she uses light and positive imagery to describe her father and bring him to life again , and she has a little hope. The image of rebirth has its own significance in this study and we illustrate it in two of her poems. This study discusses Eros in “Full Fathom Five” and “The Colossus” through the psychoanalytic approach.
Keywords: Eros; rebirth Sylvia Plath; Full Fathom Five; The Colossus